Positive outcomes among nursing home caregivers in Spain during the COVID-19 pandemic: A qualitative interview study - Macarena Sánchez-Izquierdo; Rodrigo García-Sánchez; María Prieto-Ursúa; Jesús Mateos-Nozal; Ángela Ordóñez-Carabaño (PLoS ONE, 2025)
The COVID-19 pandemic placed unprecedented strain on professional caregivers in nursing homes. This study aimed to explore the positive outcomes these caregivers experienced amidst the crisis. We conducted 15 semi-structured interviews with nurses, medical staff, and support personnel from two nursing homes in Spain between December 2021 and July 2022. Through qualitative content analysis, we uncovered signs of post-traumatic growth, such as enhanced problem-solving and organizational skills. A strong social support network was key to fostering this growth, easing distress, and strengthening team cohesion. Caregivers expressed a deep sense of gratitude and satisfaction in their roles, finding new meaning in their work, which contributed to resilience and a positive outlook despite ongoing challenges. These findings underscore the importance of robust support systems in caregiving environments, which can not only mitigate stress but also promote personal and professional growth. Further research should focus on sustaining these positive adaptations and developing strategies that enhance resilience and well-being for caregivers, ultimately improving care outcomes for older adults in nursing homes.